The Palgrave Handbook of Disability and Communication
XIX, 552 p. 4 illus.
Keywords: The Palgrave Handbook of Disability and Communication covers a broad spectrum of topics related to how we perceive and understand disability and the language, constructs, constraints and communication behavior that shape disability discourse within society. The essays and original research presented in this volume address important matters of disability identity and intersectionality, broader cultural narratives and representation, institutional constructs and constraints, and points related to disability justice, advocacy, and public policy. In doing so, this book brings together a diverse group of over 40 international scholars to address timely problems and to promote disability justice by interrogating the way people communicate not only to people with disabilities, but also how we communicate about disability, and how people express themselves through their disabled identity. Michael S. Jeffress, Ph.D. is a full professor and school counselor at Medical University of the Americas in St. Kitts & Nevis. He is author of Communication, Sport, and Disability: The Case of Power Soccer (2015) and editor of several volumes related to interdisciplinary disability studies, most recently Disability Representation in Film, TV, and Print Media (2021). Joy M. Cypher, Ph.D., is a full Professor of Communication Studies at Rowan University and an Eastern Communication Association Teaching Fellow. She is the Founding Coordinator of the Health and Science Communication interdisciplinary program at Rowan University, where she has won numerous teaching awards, including Rowan University's Lindback Award for Distinguished Teaching. Jim Ferris, Ph.D., is a full professor and holds the Ability Center Endowed Chair in Disability Studies at The University of Toledo. He is a poet and performance artist. He is a founding member of the Disability Issues Caucus of the National Communication Association and a past president of Society for Disability Studies. He is the author of numerous books and articles. Julie-Ann Scott-Pollock, Ph.D. is a full professor of communication studies at the University of North Carolina Wilmington. Her research focuses on performance ethnography and disabled embodiment and identity as performance. She is the author of Embodied Performance as Applied Research, Art and Pedagogy (Palgrave, 2017).